The Effect of MSG (Monosodium Glutamate) Addition on The Quality of Yoghurt Frozen Culture Starter Viewed Viability, pH Value and Acidity - Aris Sri Widati; Abdul Manab; Teguh Hadi Waluyo (Faculty of Animal Science Universitas Brawijaya, 2007)
The objective of this study was to investigate wether the effect of percentage monosodium glutamat addition on the quality of yoghurt frozen culture starter viewed viability, pH value and acidity.The experimental design used in this study was Randomised Complete Design and the treatment were four levels of monosodium glutamate concentration respectively 0% (without monosodium glutamat) 10%, 15% and 20% from medium. Each treatment were three times replicated. The research result showed that the difference of monosodium glutamate concentration Â did not gave a significant effect (P>0.05) on viability of yoghurt frozen culture starter and acidity of yoghurt made by frozen culture starter but it gave a significant effect (P<0.05) on pH value. It can be concluded that different monosodium glutamate concentration had a different quality on frozen culture starter yoghurt. The addition of monosodium glutamate up to 20% necessarily indicate increase on quality of yoghurt frozen culture starter. Keywords: culture starter yoghurt, freezing, cryoprotectant